Design of Archive Web Information System Electronic Documents in the Office Kotabaru District - Ong, Danny; Yanti, Vera Agustina; Sofyanty, Devy; Kusumandari, Suwantica (Jurnal sosial dan sains, 2025)
This study examines the challenges faced by the Kotabaru District Office in managing its document archives manually and proposes a web-based electronic archive information system (E-Arsip) as a solution. The research identifies inefficiencies in the current system, such as slow document retrieval, potential document degradation, and organizational issues. A web-based system offers a digital solution that improves access to and the preservation of archives while maintaining document authenticity. This study uses qualitative research methods, including observations, interviews, and document analysis, to design a comprehensive E-Archive system that ensures secure, efficient, and organized document management. The findings show that the system can significantly improve the office’s document handling and support the digital transformation of government administrative processes.